Aceh Tengah تطبيق وسيلة الصور في تدريس الإنشاء بمعهد الأزهر - Itawari, Ridha; Muhammad, Ismail; Safariah, Safariah (Fakultas Tarbiyah dan keguruan- UIN Ar-Raniry, 2023)
Al-Azhar is one of the boarding schools in Aceh Tengah. Based on the first observations that have been done by researchers at high school, there is a problem experienced by students, students find it difficult to reveal what is in their minds in accordance with the title given by the teacher in Insya' learning. This all appears clearly when students are required to make the story on Arabic. This study aims to determine how the activities of teachers and students at the implementation of the image media in Insya' learning, and to know how the improvement of students' ability in Insya's learning after the implementation of this image was in the central Al-Azhar middle-aged. The research approach used by researchers in this research is an experiment approach with the model (One Group Pre-Test Post Test Design). To collect data, researchers use pre-test and post-test and direct observation. The results of this study show that the implementation of the image media in Insya's learning is very good, this is indicated from the results of direct observation of teacher activities is 85%, and the results of student activities are 83.1% second is between the range of 81-100% with very good category. The application of this media can also improve student's ability in Insya' learning, based on the value of the test produced by the student with the level of the Sig. 0.323 and the post test value generated by students with the level of the Sig. 0.439, then the post test value is greater than the pre test value, it shows that the implementation of the image media can improve the student's ability in Insya' learning.